Prime-ministerial leadership rankings: the Australian experience. Issue 2 (3rd April 2022) - Strangio, Paul
ABSTRACT: Leadership ranking exercises, which have a storied history in the United States, have recently gained a foothold in Westminster democracies. In 2020, the author conducted a major survey of Australian political scientists and historians to gauge their opinion of the leadership performance of the nation's past prime ministers. Read in tandem with the results of earlier surveys, particularly that conducted out of Monash University in 2010, the 2020 rankings indicate that expert opinion about who have been Australia's most successful prime ministers is largely settled. The 2020 results also suggest that the experts believe that the policy legacy of a leader is a more important indicator of prime-ministerial success than is the longevity of office.